Choosing words: left hemisphere, right hemisphere, or both? Perspective on the lateralization of word retrieval. Issue 1 (14th January 2016) - Riès, Stéphanie K.; Dronkers, Nina F.; Knight, Robert T.
Abstract : Language is considered to be one of the most lateralized human brain functions. Left hemisphere dominance for language has been consistently confirmed in clinical and experimental settings and constitutes one of the main axioms of neurology and neuroscience. However, functional neuroimaging studies are finding that the right hemisphere also plays a role in diverse language functions. Critically, the right hemisphere may also compensate for the loss or degradation of language functions following extensive stroke‐induced damage to the left hemisphere. Here, we review studies that focus on our ability to choose words as we speak. Although fluidly performed in individuals with intact language, this process is routinely compromised in aphasic patients. We suggest that parceling word retrieval into its subprocesses—lexical activation and lexical selection—and examining which of these can be compensated for after left hemisphere stroke can advance the understanding of the lateralization of word retrieval in speech production. In particular, the domain‐general nature of the brain regions associated with each process may be a helpful indicator of the right hemisphere's propensity for compensation.